Sminthurides (Spinosella) dentospinalis n. subgen. n. sp. (Collembola). - Palissa, Alfred (Contributions to Entomology = Beiträge zur Entomologie, 1961)
A new species of Collembola: Sminthurides dentospinalis is described. The species is placed into a new subgenus: Spinosella. Nomenclatural Actsdentospinalis Palissa, 1961 (Sminthurides (Spinosella)), spec. n.